PENERAPAN STRATEGI WHOLE BRAIN TEACHING DALAM MENINGKATKAN MINAT BELAJAR IPA FISIKA SISWA KELAS VII SMPN 29 PEKANBARU - Tika Nur Amalia; Zuhdi Ma’aruf; Azhar ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study is designed to determine the increase student interest by applying the whole brains learning strategies in class VII SMP 29 Pekanbaru. The survey was conducted from October to December 2015 with the research subjects classes totaling 42 students. This type of research that is done beforehand experiment with the design of one group pretest-posttest desaign. Data collection instruments that the primary and secondary data in this study in the form of interest beginning and end of the 26-point statement. The results were obtained based on the indicators of interest: interest, attention, pleasure, curiosity, and needs. Interest rate indicator increased by 0.19, the attention indicator rose by 0.4, the indicators of fun with 0.18, curiosity indicator rose by 0.15, and the indicator is an increase of 0.25. Percentage changes in the interest rate was 7.52%. It can be to improve the application of the whole brain teaching strategies to students' interest in learning physics class IPA SMP 29 Pekanbaru on states of matter and material changes. Key Words: learning strategies, whole brain teaching, learning interest, states of matter and the changes.